Pulmonary Vein Stenosis in a Newborn: A Commonly Overlooked Diagnosis - Nathalie Jeanne Magioli Bravo-valenzuela; Guilherme Ricardo Nunes Silva; Marcela Pinto Varella (Case Reports in Cardiology)
The diagnosis of primary pulmonary vein stenosis is often overlooked because its symptoms overlap lung diseases and pulmonary arterial hypertension. Its diagnosis may be difficult because the condition is progressive and associated with other defects. We present a case of pulmonary vein stenosis in a newborn with stenosis of the left-sided common pulmonary vein, diffuse hypoplasia of the superior right pulmonary vein, and atresia of the inferior right pulmonary vein.